Diagnosis of solid waste management and characterization of collected waste and its cycle in Queimadas, PB, Brazil - Queiroz, Abílio José Procópio; Nascimento, Dayvison José Nunes do; Araújo, Narcísio Cabral de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Brazil has two federal policies that address solid waste management, the National Basic Sanitation and Solid Waste Policies, legal objects aimed at sustainability still neglected by Brazilian society. In this work, we aimed to characterize urban cleaning and solid waste management in Queimadas, PB, and the adequacy of services to what public policies require. The work was divided into the phases of questionnaire application with the residues manager, field visits to capture data and images, assessing the services related to MSW and the most evident impacts due to system failures, and characterization of collected MSW. The main failures identified were the lack of treatment of the collected MSW (about 29 tons/day) and its deposition in the dump area that had been operated for 20 years. On the plus side, waste management of heath services and construction has been done properly. More than 2/3 of MSW, according gravimetric composition, should receive other destination such as reuse and recycling, bringing several environmental benefits. Potentially noteworthy is the participation of Queimadas as a member of Consortium, because national policies in this area highlight the priority for consortium resource allocation. Queimadas MSW management needs services related to the selective collection and environmentally appropriate final disposal of these.